Amalgamated free product structure of the tame automorphism group of a free Novikov algebra of rank 2 - Б.А. Дуйсенгалиева; А.С. Науразбекова (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2020)
The article is devoted to the description the tame automorphism group of a free Novikov algebra of two generators over a field of characteristic zero. Using a representation of free Novikov algebras by differential polynomial algebras, some properties of basis words are investigated. It is also proved that the tame automorphism group of a free Novikov algebra of rank two over a field of characteristic zero admits the amalgamated free product structure of the affine automorphism group Af2(A) and of the triangular automorphism group T r2(A) with the united subgroup Af2(A) ∩ T r2(A) .